Atlas of cone beam imaging for dental applications - Miles, Dale A. ([S.l.] : Quintessence Publishing Co, Inc., 2013)
Cone beam imaging is fast becoming common place in dental practices for every specialty, and this best-selling book has been updated to reflect the ways in which cone beam computed tomography (CBCT) is being used by dental practitioners. As before, the book introduces readers to the different ways of viewing CBCT data sets and guides clinicians in identifying familiar and unfamiliar anatomical landmarks in the three planes of section (axial, sagittal, and coronal). New to this edition are chapters presenting endodontic applications of CBCT, selected cases from radiology practice, and issues of risk and liability associated with capturing CBCT data. In addition, the anatomy chapter has been updated with many new illustrations and a new section on small-volume anatomy. Comprehensive case presentations demonstrate the diagnostic and treatment-planning capabilities of CBCT in its full range of applications while at the same time highlighting situations in which traditional radiographic imaging will suffice.
Atlas of cone beam imaging for dental applications, 2nd edition -- Table of Contents -- Preface to Second Edition -- Preface to First Edition -- Acknowledgments -- Chapter 1: CBCT in Clinical Practice -- Chapter 2: Basic Principles of CBCT -- Chapter 3: Anatomical Structures in Cone Beam Images -- Chapter 4: Airway Analysis -- Chapter 5: Dental Findings -- Chapter 6: Impacted Teeth -- Chapter 7: Implant Site Assessment -- Chapter 8: Odotogenic Lesions -- Chapter 9: Orthodontic Assessment -- Chapter 10: Orthognathic Surgery and Trauma Imaging -- Chapter 11: Paranasal Sinus Evaluation -- Chapter 12: Temporomandibular Joint Evaluation -- Chapter 13: Systemic Findings -- Chapter 14: Vertebral Body Evaluation -- Chapter 15: Selected Cases from Radiology Practice -- Chapter 16: Clinical Endodontics -- Chapter 17: Risk and Liability -- Index.
Includes bibliographical references and index.
Keywords: Radiography; Stomatognathic Diseases; Cone-Beam Computed Tomography